Penerapan Terapi Aktivitas Kelompok Mengenal Halusinasi pada Gangguan Sensori Halusinasi Pendengaran: Application of Group Activity Therapy to Recognize Hallucinations in Sensory Stimulation Disorders: Auditory Hallucinations - Dewi Pratiwi; Indri Iriani; Maryam (Universitas Muhammadiyah Palu, 2023)
Mental disorders are serious mental health problems that cause cognitive and effective disturbances and hinder social functioning so that individuals are unable to carry out their daily activities. Hallucinations are perceptual distortions that are not real and occur in maladaptive neurobiological responses. The purpose of this study is to describe the application of group activity therapy